TALENTUM: SISTEMA INTEGRAL DE DESARROLLO HUMANO DE LA UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS - Miranda Castillo, Robert (2007)
Every time is more important that the organizations make a suitable management of their human resources, with the purpose of obtaining the development of their knowledge, abilities and potentialities. It is for that reason that the General Office of Personnel has implemented the Integral System of Human Development - TALENTUM, a modular and sustainable program in the long term that inhales the integral development of the technical personnel, administrative and educational that toils in the Greater National University of San Marcos.